Workers' compensation prescription medication patterns and associated outcomes. Issue 1 (2nd November 2021) - Freeman, Andrew; Davis, Kermit G.; Ying, Jun; Lang, David A.; Huth, Jeffery R.; Liu, Peihua
Abstract: Background: Opioid use in the treatment of musculoskeletal injuries is a complex decision where benefits must be balanced with risk. Previous research has shown an association between higher opioid doses and adverse health effects. The study's objective was to investigate whether opioid prescriptions are associated with increased costs and deaths through an injury mechanism or as a direct result of the opioid prescription. Methods: Data for 144, 553 deidentified Ohio Bureau of Workers' Compensation claims from 2010 to 2014 with shoulder, knee, and low back injuries were obtained and followed until 2016. Each claim had associated prescription information. Injury claims were further classified using the allowed diagnoses by single or multiple body areas affected and injury severity ("simple" or "complex"). The outcome variables were medical and indemnity costs, lost days, MaxMED (maximum claim‐prescribed daily morphine equivalent dose), and death status. Association between maximum opioid dose with deaths was determined by logistic regression analysis. Results: Several outcome variables, including claim medical and indemnity costs, and the likelihood of claimant death, showed significant associations with the MaxMED. In the analysis of claim deaths, these associations held for all claim types (except complex), even after adjusting for age, gender, surgery, and lost time. Conclusion: The association between increasing opioid doses and deaths for low‐severity diagnoses was disturbing given the lack of demonstrated efficacy of opioids for treatment of minor injuries. A focus on provider education, increased utilization of non‐opioids, and early intervention for minor soft‐tissue injuries could reduce claims costs, disability, and future deaths.